Covid-19 and the Disruption of Islamic Religiosity in Contemporary Indonesia; From Traditional Rituals to Virtual Rituals - Abd Hannan (Islamic Studies Journal for Social Transformation, 2021)
This study examines the phenomenon of disruption of religious religiosity among Muslim communities inIndonesia, as well as their acceptance of digital platform-based religious facilities during the Covid-19 pandemic.By using qualitative research methods and analysis of studies based on postmodern sociological theory, this studyobtained three findings; 1) During the Covid-19 pandemic, social activities in Indonesia experienced quite strictrestrictions and tightening of crowds, including socio-religious activities. In this regard, sacred religious activitiesthat were previously carried out openly in places of public worship such as mosques, prayer rooms, churches, wereall carried out separately and separately, turning to virtual worship through the use of digital applications such asZoom, Google meets, and the like; 2) In general, the emergence of these new rites is accepted by the majority ofIndonesian Muslims, and has even become a new religiosity phenomenon that is often found in many religiousactivities. Mainstream Muslim organizations in Indonesia, Nahdhatul Ulama, and Mumahammadiyah supportthe policy of sterilizing public places of worship. However, for the virtualization of religion, within certain limits,both of them criticize and even refuse to virtualize religion in totality, except for religious rituals that are onlycelebrations or slametans such as tahlilan and istigasah; 3) In the context of the dynamics of Islamic rites inIndonesia, the shift in religiosity among the Muslim community can be found in a number of socio-religiousactivities such as virtual tahlil, virtual tarawih, virtual haul, virtual gatherings on holidays, even religious activitiesthat have a mandatory law to be held regularly. The congregation is like the Friday prayer at the mosque.